Menyiapkan Sumber Daya Dosen dengan Tingkat Kebekerjaan Terampil: Studi Kasus Komunitas Kelas Menulis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung - Wahyudin Darmalaksana; Fitriani Fitriani; Susanti Vera; Hidayatul Fikra (UIN Sunan Gunung Djati Bandung, 2024)
This research aims to discuss optimizing the creation of skilled lecturer resources. This research uses a qualitative approach by applying the case study method. The results and discussion show that preparing skilled lecturer resources can be done through the agenda of accelerating the waiting period for work as a form of optimizing higher education management in ensuring graduate employment levels. This research concludes that optimizing higher education management in preparing lecturer resources has guaranteed the employment rate of graduates with a relatively fast waiting period for work of less than three years, this includes the suitability of graduates' fields of work as skilled lecturer resources.